Discontinuity of E-Government Service Innovation in Developing Countries: A Qualitative Study of the Pekanbaru City Government, Indonesia - Syamsul Pahmi; Agus Heruanto Hadna; Muhadjir Muhammad Darwin; Achmad Djunaedi (Technium Social Sciences Journal, 2025)
The sustainability of e-government innovation remains a major challenge in the digital transformation of the public sector, particularly in developing countries. Despite significant efforts to develop digital governance, many e-government initiatives experience discontinuity after their initial implementation. Pekanbaru City represents a clear example of this phenomenon, as only 33.5% of its e-government innovations launched between 2017 and 2023 have continued to operate. This study aims to analyze the underlying causes of e-government innovation discontinuity in local government contexts. A qualitative case study design was employed, using data collected through in-depth interviews, direct observation, and document analysis. The data were analyzed thematically based on Institutional Theory and the Technology–Organization–Environment (TOE) framework, following the steps of identifying meaning units, coding, categorizing, and formulating themes. The research was conducted over a period of three to four months. The findings reveal six key factors contributing to the discontinuity of e-government innovations: (1) infrastructure readiness and technological compatibility; (2) leadership, organizational culture, budgeting, and team coordination; (3) regulatory frameworks and vendor dependency; (4) compliance with standards, incentives, and sanctions; (5) social legitimacy and normative acceptance; and (6) organizational learning capacity and innovation effectiveness. The study contributes theoretically by strengthening the model of digital innovation sustainability through the integration of Institutional Theory and the TOE framework. Practically, it emphasizes the importance of strong institutional arrangements, consistent leadership, and cross-sectoral coordination to ensure the continuity of e-government innovations in local governance systems.